Full genome sequencing and genetic characterization of Eubenangee viruses identify Pata virus as a distinct species within the genus Orbivirus. - Manjunatha N Belaganahalli (PLoS ONE, 2012)
Eubenangee virus has previously been identified as the cause of Tammar sudden death syndrome (TSDS). Eubenangee virus (EUBV), Tilligery virus (TILV), Pata virus (PATAV) and Ngoupe virus (NGOV) are currently all classified within the Eubenangee virus species of the genus Orbivirus, family Reoviridae. Full genome sequencing confirmed that EUBV and TILV (both of which are from Australia) show high levels of aa sequence identity (>92%) in the conserved polymerase VP1(Pol), sub-core VP3(T2) and outer core VP7(T13) proteins, and are therefore appropriately classified within the same virus species. However, they show much lower amino acid (aa) identity levels in their larger outer-capsid protein VP2 (<53%), consistent with membership of two different serotypes - EUBV-1 and EUBV-2 (respectively). In contrast PATAV showed significantly lower levels of aa sequence identity with either EUBV or TILV (with <71% in VP1(Pol) and VP3(T2), and <57% aa identity in VP7(T13)) consistent with membership of a distinct virus species. A proposal has therefore been sent to the Reoviridae Study Group of ICTV to recognise 'Pata virus' as a new Orbivirus species, with the PATAV isolate as serotype 1 (PATAV-1). Amongst the other orbiviruses, PATAV shows closest relationships to Epizootic Haemorrhagic Disease virus (EHDV), with 80.7%, 72.4% and 66.9% aa identity in VP3(T2), VP1(Pol), and VP7(T13) respectively. Although Ngoupe virus was not available for these studies, like PATAV it was isolated in Central Africa, and therefore seems likely to also belong to the new species, possibly as a distinct 'type'. The data presented will facilitate diagnostic assay design and the identification of additional isolates of these viruses.